2011
DOI: 10.1080/15528030.2011.588087
|View full text |Cite
|
Sign up to set email alerts
|

Praying for Health by Older Adults in the United States: Differences by Ethnicity, Gender, and Income

Abstract: We studied praying for health using data from the 2007 National Health Interview Survey (n = 10,096), representing 89.6 million Americans ages 50+. Unadjusted analysis and multivariate logistic regression accounted for the survey design. Nearly 49.4 million older adults prayed for health. African Americans and Hispanics were more much likely to do so than whites, with adjusted odds ratios 2.79 and 1.86 (both p < .0001). Adjusted odds for women were nearly twice those of men (p < .0001). Those with lower income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…This definition is consistent with established approaches to defining the older population when studying health issues [20,21]. The Centers for Disease Control and Prevention (CDC) defines older populations as age 50 and above because this is the decade in which many major chronic disease processes begin to manifest symptoms, including arthritis.…”
Section: Age Threshold For Chronic Conditionssupporting
confidence: 55%
“…This definition is consistent with established approaches to defining the older population when studying health issues [20,21]. The Centers for Disease Control and Prevention (CDC) defines older populations as age 50 and above because this is the decade in which many major chronic disease processes begin to manifest symptoms, including arthritis.…”
Section: Age Threshold For Chronic Conditionssupporting
confidence: 55%
“…The 50-year mark is commonly used to delineate older adults since this is the decade with health-related problems often begin to manifest (Tait et al, 2011). Just over half the sample (50.8%, n = 409) was female.…”
Section: Samplementioning
confidence: 99%
“…Studies conducted with older women have shown that religious beliefs were beneficial in helping women to cope with physical illness (Conway, 1985(Conway, -1986Manfredi & Pickett, 1987;Rosen, 1982). Moreover, data from the U.S. 2007 National Health Interview Survey have indicated that women aged over 50 were nearly twice as likely as men to pray for health (Tait et al, 2011). Tait and colleagues further noted that the likelihood of praying for health was increased for older adults reporting ill health, particularly among those with musculoskeletal conditions, circulatory problems, depression, or cancer.…”
Section: Research On Older Adults' Religious Beliefs and Coping With mentioning
confidence: 99%
“…Reviews of research have indicated a link between attendance at a place of worship and a reduced risk of general mortality (Powell, Shahabi, & Thoresen, 2003). In addition, there has been a growing interest in the extent to which prayer and spirituality play a role in sustaining older Living Through the Paschal Mystery 49 adults through episodes of illness (Tait, Laditka, Laditka, Nies, & Racine, 2011). Nevertheless it has been easier to investigate the role of religious affiliation, community memberships, and religious practices than to understand how specific religious beliefs might be a source of comfort or painful questioning when coping with a life-threatening illness.…”
Section: Introductionmentioning
confidence: 99%